Pengembangan Model Proses Estimasi Biaya Konseptual Pembangunan Trotoar Complete Street Untuk Meningkatkan Akurasi Biaya - Kurniawati, Eva Andrian; Latief, Yusuf (Syntax Literate, 2025)
The conceptual cost estimation for complete street sidewalk projects represents early-stage budget forecasting, conducted when complete planning data is not yet available. This type of estimation is used by the Provincial Government of DKI Jakarta to propose sidewalk construction budgets over a five-year period through its Strategic Plan. However, the current estimation practices still exhibit a low level of accuracy, leading to inefficiencies in regional development planning and misaligned budget utilization due to shifting priorities. This issue stems from several influencing factors in the estimation process, including scope quality, information quality, estimation procedures, estimator competence, uncertainty, cost information, government regulations, and procurement methods. To improve the accuracy of conceptual cost estimation, it is necessary to develop a model that describes the relationships among these factors and their influence on estimation accuracy. This model can help identify key variables and dominant factors that significantly affect cost estimation outcomes. Using the SEM-PLS method, the study reveals 11 significant relationships among variables involved in the conceptual cost estimation process for complete street sidewalks, with an R² value of 0.308. The analysis also identifies five dominant factors influencing estimation accuracy: information quality, estimation procedures, estimator competence, government regulations, and procurement. Based on these findings, a series of improvement strategies were formulated and compiled into the Technical Guidelines for Conceptual Cost Estimation of Complete Street Sidewalk Projects by the DKI Jakarta Provincial Government.